2001
DOI: 10.1086/322604
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, Incidence, and Susceptibility of Bacterial Bloodstream Isolates from 519 Bone Marrow Transplant Patients

Abstract: Bacteria remain an important cause of infection in bone marrow transplants. To examine shifts in the etiology and susceptibility of bacterial isolates from transplants, we reviewed the incidence and susceptibility of blood isolates during a 7-year period. The infection rate fell dramatically during this time. Gram-positive organisms were isolated more often than gram-negative organisms, but the trend is reversing. Streptococci surpassed staphylococci for 5 years as the leading pathogen. Increasing resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
182
8
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(228 citation statements)
references
References 26 publications
31
182
8
7
Order By: Relevance
“…This finding is in line with other studies that have found a higher risk of BSI in this specific group of transplant recipients. 3,7 During the pre-engraftment period, we identified the presence of neutropenia, a central venous catheter and severe mucositis as important risk factors for BSI. During the pre-engraftment phase it is likely that mucosal damage allows bacteria to enter the bloodstream and the lack of neutrophils hampers their effective clearance, thus leading to BSI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in line with other studies that have found a higher risk of BSI in this specific group of transplant recipients. 3,7 During the pre-engraftment period, we identified the presence of neutropenia, a central venous catheter and severe mucositis as important risk factors for BSI. During the pre-engraftment phase it is likely that mucosal damage allows bacteria to enter the bloodstream and the lack of neutrophils hampers their effective clearance, thus leading to BSI.…”
Section: Discussionmentioning
confidence: 99%
“…One trial showed similar antibody responses with vaccination started at 3 months (early) and 9 months (late) post transplant. 7 Thus, early vaccination may be preferred as it may protect against both late and early pneumococcal disease. It should be noted that early vaccination may not prime for a PPSV23 boost as efficiently as late vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune reconstitution of T-and B-cell compartments following allogeneic transplantation may require as long as 12-24 months. The slow process of immune reconstitution together with post-engraftment immunosuppression creates an immunologic environment whereby the host is susceptible to opportunistic infections [54][55][56] as well as virally induced malignancies [57,58]. Recipients of unrelated donor or HLA non-identical transplants appear to have a higher rate of infectious complications than recipients of matched sibling allogeneic grafts [59][60][61].…”
Section: Ucb Basic Biology and Implications For Immune Reconstitutionmentioning
confidence: 99%
“…Each CLABSI puts patients at greater risk of complications including: sepsis, endocarditis, multidrug-resistant (MDR) bacteria, thrombosis and malnutrition which may lead to more hospital stays, increased costs of care, and decreased quality of life. 2,3 Additionally, most bloodstream infections require catheter replacement for optimal management. 4 Ethanol lock therapy (ELT) is a proposed method to reduce CLABSIs requiring hospitalizations and associated line replacements by preventing catheters from becoming colonized.…”
Section: Role Of Ethanol Locks In Reducing Bloodstream Infections In mentioning
confidence: 99%